Combined transcervical and orbitozygomatic approach for the removal of a nasopharyngeal adenocarcinoma. Issue 2 (April 2016) - Masuda, Muneyuki; Fukushima, Junichi; Fujimura, Akiko; Uryu, Hideoki
Abstract: Objective: In some cases, the exposure and safeguarding of the internal carotid artery (ICA) are not easy by the maxillary swing approach that is used as a mainstay for the removal of nasopharyngeal tumors. To address this issue, we have developed a new combined transcervical and orbitozygomatic approach. Methods: A nasopharyngeal adenocarcinoma arose in a 52-year-old patient and occupied the right middle skull base extending to the ICA. We first identified and dissected the ICA from the posterolateral part of the tumor using a transcervical approach. Then, the tumor was approached and removed by an orbitozygomatic technique with hemifacial dismasking. The surgical defect was filled using a temporal muscle flap, which was divided into two parts according to the blood supply from either the anterior or the posterior deep temporal artery. Results: The postoperative course was uneventful and favorable cosmetic results were obtained. The patient has been free of carcinoma for more than 40 months after the surgery. Conclusion: Our new combined approach might be a good option for selected patients with nasopharyngeal tumors.